Compliance with treatment in adult patients with cystic fibrosis. Issue 1 (January 1996) - Conway, S. P.; Pond, M. N.; Hamnett, T.; Watson, A.
Abstract : BACKGROUND: Patients with chronic disease comply with about 50% of their treatment. The complex and time consuming daily drug regimens needed in the care of adult patients with cystic fibrosis encourage non-compliance with prescribed treatments. Understanding the reasons for, and the extent of, non-compliance is essential for a realistic appraisal of the patient's condition and sensible planning of future treatment programmes. METHODS: Patients were invited to complete a questionnaire which asked about their compliance with daily treatment. The data were used to calculate a compliance score, the percentage of prescribed treatment taken, and to examine patient attitudes to each individual prescription. An assessment score derived from consultant, cystic fibrosis research fellow, specialist nurse, and physiotherapist ratings of patient compliance was compared with the compliance score. Both scores were correlated with patient characteristics and disease severity, and the compliance score was also correlated with the patient's knowledge of cystic fibrosis. RESULTS: More than half the patients claimed to take more than 80% of their treatments. Compliance with individual treatments varied according to their perceived unpleasantness and degree of infringement on daily activities. The most common reason given for omitting treatment was forgetfulness. Professional carers were poor judges of patient compliance. There was no correlation between compliance and patients' sociodemographic characteristics or their knowledge about cystic fibrosis. CONCLUSIONS: Non-compliance is universal and should be recognised as normal behaviour. There are no reliable criteria for predicting any patient's level of compliance. Treatment protocols should be planned around individual patient's requirements, modifying treatment ideals where necessary according to the exigency and pattern of that patient's lifestyle.